Analisa Pengesahan Rancangan Undang-Undang Pembatasan Transaksi Uang Kartal - Aqil Tajuddin Zhahir; Ariesta Chandra Perdana; Claudia Theresia Sihotang; Muhammad Galih Sampurno (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
The Bill on the Limitation of Cartal Money Transactions (RUU PTUK) is a regulation regarding the limitation of cartal money transactions to 100 million rupiah in a day either in one transaction or several times, more than that must use digital money. The purpose of this bill is to reduce circulation and emphasize counterfeit money and reduce corruption activities. This paper aims to identify the problems and impacts of the passage of the PTUK Bill on corruption and money politics in Indonesia. The PTUK Bill in its application requires public participation to support the PTUK Bill, besides that the public needs to understand the consequences of money politics on the sustainability of government.